Use of Dietary Supplements in Cancer: A Single-Institution Study - Kamian, Shaghayegh; Mafi, Ahmad R (Reports of Radiotherapy and Oncology, 2019)
Background: Many patients with cancer tend to use vitamin supplements alongside their conventional cancer treatments. They have the presumption that vitamins can help them feel better or fight the disease. Objectives: The aim of this study was to determine the prevalence of vitamin use among cancer patients in a referral cancer center in Tehran, Iran. Methods: Two hundred cancer patients who were undergoing outpatient chemotherapy or chemo-radiation were chosen. The data about the use of vitamins and whether they had been prescribed by their physician were collected by a questionnaire. Results: Among the patients who were being treated with chemotherapy alone (81.5% of the cases), 20.4% reported regular use of vitamins. This figure for the remaining 18.5% who were undergoing chemoradiation was 23.7%. The interesting finding was that in 43.9% of the cases who were taking vitamins, it was prescribed by the treating oncologist. More than half (52.5%) of the patients who were taking vitamins had no other medical illness apart from cancer. Multivitamin capsules were the most commonly used form of vitamins. Conclusions: More than 20% of our patients took vitamins regularly. In more than 40% of these cases, vitamin supplements had been prescribed by the treating physician. As there is some evidence that vitamins can interfere with chemotherapy and probably radiotherapy treatments, it would be prudent for oncologists to prescribe them more cautiously for the cancer patients who are under active treatment.